Cellular prion protein regulates the differentiation and function of adipocytes through autophagy flux. (5th February 2019) - Jeong, Jae-Kyo; Lee, Ju-Hee; Kim, Sung-Wook; Hong, Jeong-Min; Seol, Jae-Won; Park, Sang-Youel
Abstract: The role of autophagy modulation in adipogenic differentiation and the possible autophagy modulators targeting adipogenesis remain unclear. In this study, we investigated whether normal cellular prion protein (PrP) is involved in the modulation of autophagy and affects adipogenic differentiation in vivo and in vitro. Surprisingly, autophagy flux signals were activated in the adipose tissue of prion protein-deficient mice and PrP-deleted 3T3-L1 adipocytes. The activation of autophagy flux mediated by PrP deletion was confirmed in the adipose tissue via transmission electron microscopy. Adipocyte differentiation factors were highly induced in prion protein-deficient adipose tissue and 3T3-L1 adipocytes. In addition, deletion of prion protein significantly increased visceral fat volume, body fat weight, adipocyte cell size, and body weight gain in Prnp -knockout mice and increased lipid accumulation in PrP siRNA-transfected 3T3-L1 cells. However, the overexpression of prion protein using adenovirus inhibited the autophagic flux signals, lipid accumulation, and the PPAR-γ and C/EBP-α mRNA and protein expression levels in comparison to those in the control cells. Our results demonstrated that deletion of normal prion protein accelerated adipogenic differentiation and lipid accumulation mediated via autophagy flux activation. Highlights: Autophagy flux was activated in adipose tissue of prion protein-deficient mice. Adipogenic factors were highly induced in prion protein-deficient adipose tissue. Prion protein overexpression inhibited the autophagy-mediated lipid accumulation. Prion protein regulates adipogenic differentiation via autophagy flux signals.